Responding to mental health statutory drivers: experience of a low intensity cognitive behavioural therapy programme. (20th November 2015) - Mills, R.; Mowlds, W.; Dyer, K. F. W.; Corr, P.; Kavanagh, M.
Abstract : Objectives: Stress control (SC), a brief psycho-education course, was implemented to increase access to psychological therapies in line with Northern Irish mental health service statutory drivers. The first aim of this study was to gauge the efficacy of SC in a robust manner with clinical significance testing. The second aim was to assess whether demographics traditionally 'hard-to-reach' – males, younger adults and those from deprived areas – accessed SC. The third aim was to elucidate what prompted their access and the experiences of attendees at SC. Methods: Attendees at SC were 170 adults over six iterations of the course. Pre- and post-questionnaires included the Depression Anxiety Stress Scales – 21, captured demographic details and qualitative feedback, which was subject to a mixed-methods analysis. Results: SC attendees reported significant decreases on depression, anxiety and stress sub-scales post-intervention. Moreover, 38.71% ( n =36) of attendees who completed SC exhibited clinically significant improvement afterwards on one or more sub-scale. Attendance figures for males, younger adults and those classified as socioeconomically deprived were modest. Patterns within the data suggested prospective success for targeting these cohorts. Conclusions: SC attracted people in need of mental healthcare input and affected quantifiable change within those people's lives, while satisfying statutory demands for service delivery in an accessible community context. Recommendations to increase engagement with those traditionally 'hard-to-reach' for psychological services are provided, which, if implemented, have the potential to achieve further compliance with Northern Irish mental health statutory drivers.